Clinical profile of children aged 2 months to 60 months presenting with wheeze in a tertiary medical centre - Mondal, Arup Ratan; Singh, Ch Shyamsunder; Devi, Moirangthem Meenakshi; Laishram, Cindy; Kambiakdik, T. (International Journal of Contemporary Pediatrics, 2020)
Background: Wheezing is common throughout infancy and childhood except in the neonatal period where it is relatively rare. By 10 years of age, about 19% of children experience wheezing with an average onset at 3 years of age. This study was aimed to identify the diverse factors associated with wheezing in children aged 2 months to 60 months and to study clinical profile along with short term outcome of the same. Methods: It was a hospital based cross-sectional study carried out in the Department of Paediatrics, Regional Institute of Medical Sciences Hospital (RIMS), Imphal, Manipur. The Study population consisted of randomly selected 131 children aged 2 months to 60 months who were admitted in Paediatrics ward with the symptom of wheezing. Results: Authors found that age below 12 months, male sex, low socioeconomic conditions and artificial breastfeeding practices were important risk factors for wheeze. Conclusions: Wheezing is accountable for a high demand of medical consultations and emergency care services with relatively high rates of hospitalization. Along with ARI, it plays an important role in infant mortality. In Manipur, it is being observed that increasing number of children with wheezing are attended by paediatricians in ED, OPD and ward, thereby proving an added burden to the younger age group. Therefore proper health education and counselling of parents, promotion of exclusive breast feeding and improvement of socioeconomic status can play a vital role in preventing occurrence of wheeze among the children.